Cost overruns of public sector construction projects: a developing country perspective. Issue 1 (13th May 2019) - Asiedu, Richard Ohene; Adaku, Ebenezer
Abstract : Purpose: Cost overrun of construction projects has been a key concern for all stakeholders of projects for many decades now. Many studies have been done in the past and continue to be done currently to understand the underlying causes of construction project cost overruns. However, the empirical evidence of the causes seem not be clear due to the silo approach in understanding the causes of construction project cost overruns. The purpose of this paper is to take the debate a step forward by providing an understanding of the causes of project cost overrun from a system's perspective, especially from a less researched environment. Design/methodology/approach: Data were collected and analysed from 131 respondents who were mainly involved in construction works in public procurement entities in Ghana. A two-staged approach was employed in collecting data from the respondents. The first stage involved an interview session with key informants in the construction industry in Ghana to ascertain the detailed causes of cost overrun of construction projects. The second stage focussed on the validation of these detailed factors by a wider stakeholder group through questionnaires. Factor analysis was employed to consolidate these detailed factors into major causes of construction project cost overruns. Findings: The results show that there are primarily four major causes of most public sector construction projects cost overruns. These four major causes of cost overruns are poor contract planning and supervision; change orders; weak institutional and economic environment of projects and lack of effective coordination among the contracting parties. Originality/value: The study provides more insights as to the critical and major factors that underpin public sector construction projects cost overruns and more importantly provides a basis for common treatment of the multiple risk factors engendering public sector construction projects cost overruns.